2010
DOI: 10.3969/j.issn.1004-4132.2010.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Integrating dual-role variables in data envelopment analysis

Abstract: Memristor with memory properties can be applied to connection points (synapses) between cells in a cellular neural network (CNN). This paper highlights memristor crossbar-based multilayer CNN (MCM-CNN) and its application to edge detection. An MCM-CNN is designed by adopting a memristor crossbar composed of a pair of memristors. MCM-CNN based on the memristor crossbar with changeable weight is suitable for edge detection of a binary image and a color image considering its characteristics of programmablization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…His proposed model modified the limitation of Cook et al's (2006) model. Based on this model, Farzipoor Saen (2011b), Farzipoor Saen (2010a, b, c;2011a, b, c) and Yang et al (2010) extended several dual-role models in the presence of stochastic data, imprecise data, and weight restrictions and applied them to assess 3PL providers, international market, advertising media, technology, and production system. Nonetheless, Mahdiloo et al (2011) mentioned that the conventional models (such as Cook et al, 2006;Farzipoor Saen, 2010c) deal with dual-role factor as non-discretionary (uncontrollable) criteria, whereas there might be dual-role factor which is under control of management.…”
Section: Dual-role Factormentioning
confidence: 99%
“…His proposed model modified the limitation of Cook et al's (2006) model. Based on this model, Farzipoor Saen (2011b), Farzipoor Saen (2010a, b, c;2011a, b, c) and Yang et al (2010) extended several dual-role models in the presence of stochastic data, imprecise data, and weight restrictions and applied them to assess 3PL providers, international market, advertising media, technology, and production system. Nonetheless, Mahdiloo et al (2011) mentioned that the conventional models (such as Cook et al, 2006;Farzipoor Saen, 2010c) deal with dual-role factor as non-discretionary (uncontrollable) criteria, whereas there might be dual-role factor which is under control of management.…”
Section: Dual-role Factormentioning
confidence: 99%
“…However, there might be dual-role factors which are completely discretionary. Decision variable is an important element in DEA framework, and the cognition of decision variable improves the progress of DEA-based theories and approaches (Yang et al, 2010). Farzipoor Saen (in press) addresses that, in traditional DEA, the decision-maker decides which criteria are inputs and which are outputs.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Cook et al (2006) developed a new model that has no above-mentioned limitations. Yang et al (2010) analysed the structure and properties of the production systems and suggested a DEA model which considers dual-role factors. Farzipoor Saen (2010a) proposed a new model for selecting third-party reverse logistics (3PL) providers in the presence of multiple dual-role factors.…”
Section: Introductionmentioning
confidence: 99%